Impact of flavouring substances on the aggregation behaviour of dissolved barley β-glucans in a model beer. (5th June 2016) - Kupetz, M.; Sacher, B.; Becker, T.
Highlights: Influence of hydrophobic substances on the structure of β-glucan could be shown. Increase of molar mass with higher amount of volatiles. Enlargement independent on lipophilicity (log P value) of volatiles. Aggregation depends on geometry and type of functional groups of volatiles. Abstract: Structural polymers such as cereal β-glucan may cause various processing problems in beverage industry depending on concentration, molar size distribution and agglomeration behaviour. In this context, influences of the beer volatiles dodecanoic acid, octyl butanoate, ethyl decanoate and decyl acetate on molar mass and radii of barley β-glucan were investigated in ethanolic (4% w/w) model solution. After addition of 100 mg/l ethyl decanoate and decyl acetate to the β-glucan solution, a wider-ranging molar mass distribution could be observed by means of asymmetric field-flow-fractionation. Due to agglomeration, average molar mass of β-glucan standard ( M W = 6.8 × 10 6 g/mol) increased by 2 × 10 6 g/mol ( P < 0.05) in solution containing decyl acetate. Furthermore, a significant growth ( P < 0.05) from 86 to 102 nm in gyration radius was measured. The obtained results elucidate the importance of fatty acid derived flavouring substance composition in beer regarding the aggregation behaviour of β-glucan.